Factibilidad para la creación de una microempresa procesadora de leche de soya en la parroquia San Carlos, canton Quevedo provincia de los Rios - Velázquez de la Cruz, Irene Marlene (2011)
The present investigation fulfilled in Company Private American Seguridad Ameripriv Cía. Ltda. of the Canton Quevedo, same who devotes itself to offer service of private safety there are different companies of the way, the Wood is located in the citadel there is quiet Milton Reyes Callejón S/n. of the Canton Quevedo, Province The Rivers. The work investigativo had a duration of 6 months. One of the activities of major transcendency of organization and methods, consists of the analysis of the administrative in force procedures or of the definition of the circuits and the new activities that a constituted company faces; it is here where an administrative procedure involves the definition of functions and tasks for every area that is structured an organization, with clear and precise specifications of the treatment or course of action to continue. The specific aims raised for the company Ameripriv were the following ones: To identify the current processes of the structure organizacional and functional, to determine the existing failings in the process organizacional and functionally, develops the offer of reengineering for the company Private American Seguridad Ameripriv Cia. Ltda. of the Canton Quevedo. The methodological addressing was orientated in the employment of two types of Investigation: Of field, in that one used the technologies of the survey, the interview and observation where the methods were applied Deductively - Inductively and Analytical - Synthetically and Bibliographical Investigation, which support is the information obtained by means of primary and secondary sources rested on methods. To know Ameripriv's situational way his employees were polled, a questionnaire was in use; where one emphasizes that of the persons who work in the company it has the fluctuating age from 26 to 35 years, that the years that go working the operative personnel is less than one year with 63.04 %, the problems that more affect the harmony in the work of the operative personnel it is the salary with 73.91 %, the training that they receive in the main corresponds to 84.78 % rarely 80.43 % indicates not to possess a manual of functions, 100 % indicated that they agree with that a reengineering is realized because it will allow the growth of the company The manual of administrative procedure was elaborated as a mechanism of control to strengthen the efficiency of the business management in all the areas that shape it, beside realizing the description of every working place, and the responsibility of every employee.